2013
DOI: 10.2478/pjct-2013-0010
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Performance of Hybrid Photolysis-DCMD and Photocatalysis-DCMD Systems Utilizing UV-C Radiation for Removal of Diclofenac Sodium Salt From Water

Abstract: The removal of a non-steroidal anti-infl ammatory drug (NSAID) diclofenac sodium salt (DCF, C 14 H 10 Cl 2 NNaO 2 ) from water in two hybrid systems coupling photolysis or photocatalysis with direct contact membrane distillation (DCMD) is presented. A UV-C germicidal lamp was used as a source of irradiation. The initial concentration of DCF was in the range of 0.005-0.15 mmol/dm 3 and the TiO 2 Aeroxide® P25 loading (hybrid photocatalysis-DCMD) ranged from 0.05 to 0.4 g/dm 3 . Regardless of the applied hybrid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 41 publications
2
12
0
Order By: Relevance
“…93–94% NAP was removed regardless of TiO 2 loading. We obtained similar results during our earlier investigations on the removal of diclofenac from distilled water . We found that DCF decomposition rate during the first hour of the hybrid photocatalysis–DCMD process was decreasing with increasing photocatalyst loading from 0.05 to 0.4 g dm −3 .…”
Section: Resultssupporting
confidence: 85%
See 2 more Smart Citations
“…93–94% NAP was removed regardless of TiO 2 loading. We obtained similar results during our earlier investigations on the removal of diclofenac from distilled water . We found that DCF decomposition rate during the first hour of the hybrid photocatalysis–DCMD process was decreasing with increasing photocatalyst loading from 0.05 to 0.4 g dm −3 .…”
Section: Resultssupporting
confidence: 85%
“…There are also other configurations of PMRs, in which photocatalysis is coupled with DCMD dialysis or pervaporation . The first from the above mentioned configurations was proposed by our group.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a successive work, the same authors (Mozia, Darowna, Przepi orski, & Morawski, 2013) reported the removal of a nonsteroidal anti-inflammatory drug (diclofenac sodium salt [DCF]) from water in two hybrid systems coupling photolysis or photocatalysis with DCMD. The results are summarized in Figure 7.14 in terms of TOC amounts in distillate (permeate) at the end of various experiments in comparison with the initial and final amounts of organic carbon in feed solutions.…”
Section: Applications Of Pmrs For Water Treatmentmentioning
confidence: 99%
“…The results obtained by Mozia and Morawski (2012) and Mozia et al (2013) showed that, because the MD efficiently separated not only TiO 2 particles, but also organic contaminants present in feed solution, the PMR using DCMD represents a promising method for treatment of waters containing pharmaceuticals. Low permeate (distillate) flux assured relatively long residence time of contaminants, which resulted in high effectiveness of their photodegradation.…”
Section: Applications Of Pmrs For Water Treatmentmentioning
confidence: 99%